“Juegos recreativos para el desarrollo del equilibrio motriz en los niños de Educación Inicial” - Gutiérrez Camacho, Estela Marisol (2024)
Recreational games are activities that seek happiness, entertainment and free expression of children in Initial Education, however, in the diagnostic project linked to the name "Recreational games for the development of motor balance in children in Initial Education" , with the qualitative methodology and the interview instruments and the observation sheet applied to the children of Initial Education, determine that there is a deficiency in the development of motor balance due to which the teachers are unaware of this type of recreational games. The objective of this research in the face of the evident problems was to design recreational games for the development of motor balance in early education children and respond to this observed need, based on the constructivist approach where recreational activities become a tool. pedagogical for infants. This proposal contains 15 recreational games to reinforce the development of balance in Early Education children, which was validated by experts and users, rating each of the activities in the proposal presented as excellent. Finally, these specific activities for the development of motor balance and recreational games have proven to be a comprehensive proposal that allows addressing the needs of the children of the educational units of the Angamarca Parish.